Evaluation of the Level of Knowledge of Housewives Regarding How to Store Medicines in Galesong Village, Takalar Regency (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Background. Hospitals can create a positive feedback cycle that can significantly increase patient loyalty by combining an effective marketing mix strategy with good CRM practices. By meeting the needs and wants of patients well, hospitals can build long-term relationships, foster trust, and strengthen patient loyalty. Therefore, hospitals must have the right business strategy to be able to survive and be superior to their competitors. Research Objective is to determine the influence of marketing mix and customer relationship management simultaneously on the loyalty of outpatients at Lanto Dg. Pasewang Regional General Hospital in 2024. Research Method used in this study is a quantitative research method with a cross-sectional approach. The population in this study was 61,794 outpatients and a sample of 371 respondents using the Slovin formula. The data of this study was obtained through a questionnaire that has been tested for validity and reliability. The analysis techniques used are univariate analysis, bivariate analysis with chi-square test and multivariate analysis with multiple linear regression test with the help of SPSS application. Results and Conclusions of this study show that marketing mix has a significant effect on patient loyalty (p = 0.000), the results of the T test obtained (0.005 < 0.050) customer relationship management have a significant effect on patient loyalty. Meanwhile, the results of the F test obtained a value of F-calculated 31.564 > F-table 3.02, it can be concluded that there is an influence between Marketing Mix and Customer Relationship Management simultaneously on Outpatient Loyalty of Lanto Dg. Pasewang Regional General Hospital in 2024. Recommendations for hospitals to continue to maintain the quality of their services both in terms of marketing mix and customer relationship management in order to create patient loyalty.